2009
DOI: 10.1007/s12010-009-8813-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on the Activity of Tannase from Aspergillus awamori MTCC9299

Abstract: Tannase from Aspergillus awamori MTCC 9299 was purified using ammonium sulfate precipitation followed by ion-exchange chromatography. A purification fold of 19.5 with 13.5% yield was obtained. Temperature of 30 degrees C and pH of 5.5 were found optimum for tannase activity. The effects of metals and organic solvents on the activity of tannase were also studied. Metal ions Mg(+2), Mn(+2), Ca(+2), Na(+), and K(+) stimulated the tannase activity, while Cu(+2), Fe(+3), and Co(+2) acted as inhibitors of the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 18 publications
4
26
0
Order By: Relevance
“…tannases with an optimum activity at a pH of 5.5. Tannases from Aspergillus awamori and Aspergillus heteromorphus also are optimally active at pH 5.5 [32,33]. A. awamori nakazawa exhibited optimum activity at pH 5.0 [34], and tannase from Penicillium variable was found to be stable at pH range of 3.0-8.0 [35].…”
Section: Discussionmentioning
confidence: 98%
“…tannases with an optimum activity at a pH of 5.5. Tannases from Aspergillus awamori and Aspergillus heteromorphus also are optimally active at pH 5.5 [32,33]. A. awamori nakazawa exhibited optimum activity at pH 5.0 [34], and tannase from Penicillium variable was found to be stable at pH range of 3.0-8.0 [35].…”
Section: Discussionmentioning
confidence: 98%
“…The synthesis of the enzyme was reduced in SR medium maintained under agitation (16.31 U/mL). Czapeck medium is one of the most cited for the production of tannase by fungi, such as A. awamori MTCC9299 [29], A. niger GH1 [30] and A. oryzae [25]. Adams medium was more favorable for the enzyme production by A. japonicus 246A (19.8 U/mg of protein) and Aspergillus sp.…”
Section: Effect Of Culture Mediummentioning
confidence: 99%
“…Chhokar et al (2010) reported that maximum production of tannase was achieved after 48 h of fermentation using Aspergillus heteromorphus MTCC 8818. However, observed maximum production only after 98 h using Penicillium atramentosum.…”
Section: Resultsmentioning
confidence: 99%
“…Chhokar et al (2010) reports a yield of 19.29% when purified derived from 1% concentration of tannic acid while using A. heteromorphus MTCC 8818. Raaman et al (2010) used a tannic acid concentration of 1.5% (89 U/mL) along with Paecilomyces variotii.…”
Section: Resultsmentioning
confidence: 99%